2016
DOI: 10.1002/cctc.201600280
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Active Magnetite Nanoparticles Supported on Charcoal for Facile Synthesis of Alkynyl Selenides by C−H Activation

Abstract: Magnetite (Fe3O4) nanoparticles supported on charcoal, graphene, or SBA‐15 were prepared by a simple solid‐state grinding technique and subsequent thermal treatment. The Fe3O4 nanoparticles supported on activated charcoal exhibited high catalytic activity and furnished good yields of the alkynyl selenide product in the cross‐coupling reaction of diphenyl diselenide and alkynes through activation of C−H and Se−Se bonds under ecofriendly conditions, surpassing traditional copper‐based catalysts to effect the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…described a useful cross‐coupling reaction of diphenyl diselenide and alkynes through activation of C−H and Se−Se bonds employing the Fe 3 O 4 NPs supported on activated charcoal (Fe 3 O 4 @C) under eco‐friendly conditions (Scheme 42). [165] They fabricated three catalysts namely Fe 3 O 4 @C, Fe 3 O 4 @SBA‐15 and Fe 3 O 4 @graphene by a simple solid‐state grinding technique and followed by thermal treatment. It was observed that the Fe 3 O 4 @C catalyst exhibited high catalytic activity in terms of good yields of the coupling product.…”
Section: Functionalization Of C−h Bond Via C−h Activationmentioning
confidence: 99%
“…described a useful cross‐coupling reaction of diphenyl diselenide and alkynes through activation of C−H and Se−Se bonds employing the Fe 3 O 4 NPs supported on activated charcoal (Fe 3 O 4 @C) under eco‐friendly conditions (Scheme 42). [165] They fabricated three catalysts namely Fe 3 O 4 @C, Fe 3 O 4 @SBA‐15 and Fe 3 O 4 @graphene by a simple solid‐state grinding technique and followed by thermal treatment. It was observed that the Fe 3 O 4 @C catalyst exhibited high catalytic activity in terms of good yields of the coupling product.…”
Section: Functionalization Of C−h Bond Via C−h Activationmentioning
confidence: 99%
“…Fe 3 O 4 NPs supported on charcoal, (0.5 mol % Fe 3 O 4 /C) were also studied by the same group in the cross coupling reactions between alkynes and diselenides to obtain alkynyl selenides. 229 Pd NPs have been used in halogenation reactions through C− H activation. In 2015, Korwar et al expanded the application of their catalytic system composed of Pd NPs supported on 233 Pd NPs with a mean size of around 2 nm were immobilized into two porous MOFs of different nature, [Pd@MIL-88B-NH 2 (Fe-MOF) and Pd@MIL-101-NH 2 (Cr-MOF)].…”
Section: C−h Bond Activation For Chalcogenation and Halogenation In 2...mentioning
confidence: 99%
“…The role of the oxygen was to regenerate the disulfide or the diselenide. Fe3O4 NPs supported on charcoal, (0.5 mol% Fe3O4/C) were also studied by the same group in the cross coupling reactions between alkynes and diselenides to obtain alkynyl selenides 229. Pd NPs have been used in halogenation reactions through C-H activation.…”
mentioning
confidence: 99%
“…The importance of the latter materials for emerging technologies, for instance, those related to energy or medical diagnostics, calls for this development. Whereas solvent-free milling has previously been used to access diverse types of nanosized materials (including supported metal NPs; ,, metal oxide, nitride, and sulfide NPs; carbon-based NPs; and porous nanocomposites) , such work has been largely based on top-down mechanochemical routes, i.e., through energy-demanding particle size reduction of bulk materials. Such comminution techniques can yield particles in the size range 10–50 nm, but they cannot provide the required level of size and shape control required for high end applications. , …”
Section: Introductionmentioning
confidence: 99%